Gen Z's Self-Expression and Digital Identity Strategies on Social Media X: A Quantitative Study of Communication Styles and Audience Engagement - Nurrachmah, Sitti (Riviera Publishing, 2025)
This study explores the self-expression strategies and digital identity formation of Generation Z on social media platform X, focusing on communication styles and audience engagement. As digital natives, Gen Z actively utilizes social media not only as a tool for interaction but also as a medium to construct, negotiate, and display their personal and collective identities. Through a quantitative approach, this research examines the relationship between various communication styles—such as authenticity, humor, and visual storytelling—and the level of audience engagement, including likes, comments, shares, and follower growth. The data were collected from 250 Gen Z users through online surveys and analyzed using statistical methods to identify patterns and correlations. The findings reveal that authentic and visually appealing content significantly increases audience interaction, while humor enhances relatability and connection with followers. This study highlights the importance of strategic self-expression for digital identity management and provides insights for content creators, marketers, and social media practitioners seeking to engage Gen Z audiences effectively.